Investigation of Toxoplasma gondii in semen, testicle and epididymis tissues of primo-infected cats (Felis catus) - Teixeira, Weslen Fabricio Pires [UNESP]; Tozato, Maria Eduarda Gonçalves [UNESP]; Pierucci, Julia Cestari [UNESP]; Vital, Giovana Pavão [UNESP]; Cruz, André Cayeiro [UNESP]; Lopes, Welber Daniel Zanetti [UNESP]; Cursino, Marina Suzuki [UNESP]; Joaquim, Samea Fernandes [UNESP]; Soares, Vando Edésio [UNESP]; Langoni, Helio [UNESP]; Bresciani, Kátia Denise Saraiva [UNESP]; Costa, Alvimar José da [UNESP] (My University, 2017)
This study aimed to investigate the presence of Toxoplasma gondii in semen, testicle and epididymis tissues of cats experimentally infected by this coccidium. A total of 12 male felines without a definite breed that were of reproductive age and serologically negative for T. gondii were selected and distributed to the following three experimental groups: GI, inoculated with 600 tissue cysts of the P strain of T. gondii (isolate III); GII, inoculated with 2 × 105 tachyzoites of the RH strain (isolate I); and GIII, not inoculated (control group). Prior to inoculation (day −7 and 0) and on post inoculation days (PIDs) 7, 14, 21, 28, 42, 56, and 70, all felines were subjected to assessments of anti-T. gondii IgG by indirect immunofluorescence (IIF) and assessments of parasitemia. Collection of semen (electroejaculation) was performed on the specified dates, followed by nested PCR and bioassays in mice to detect T. gondii. On PID 70, all 12 felines were orchiectomized, and the presence of the parasite in the testicles and epididymides was evaluated by nested PCR, murine bioassay, and histopathological and immunohistochemical analyses. All felines inoculated with T. gondii (GI and GII) seroconverted to the toxoplasmic infection after PID 14; on PID 7, seroconversion of three felines (P4, RH2 and RH4) could observed, and all exhibited detectable titers by PID 64. The GII felines exhibited greater serological titers compared with GI felines. The maximum serological titer (IgG) was observed in feline RH3 (titer 1024), while in other experimental felines, a maximum titer of 256 was detected. Parasitemic peaks were diagnosed in all felines of groups I and II from PIDs 7–42. A total of five parasitemic peaks were diagnosed in GI and nine in GII. In none of the experimental time points was the presence of T. gondii diagnosed in seminal samples collected from the felines or in the testicle or epididymis tissues collected from these animals. Thus, sexual transmission in domestic cats does not appear to be a major route of T. gondii infection, possibly demonstrating the tendency of this protozoan to develop a response directed to the formation and excretion of oocysts in the feces of these definite hosts, which act as its main route of perpetuation in the environment.
Keywords: Felines; PCR; Sexual transmission; Tachyzoites; Toxoplasmosis